Folic Acid Supplement Use and Increased Risk of Gestational Hypertension. Issue 1 (July 2020) - Li, Qian; Xu, Shangzhi; Chen, Xi; Zhang, Xu; Li, Xiating; Lin, Lixia; Gao, Duan; Wu, Meng; Yang, Sen; Cao, Xiyu; Tan, Tianqi; Hu, Wenqi; et al.
Abstract : Current results regarding the effect of folic acid (FA) supplement use on gestational hypertension (GH) and preeclampsia are limited and inconsistent. We aimed to investigate whether FA supplement use was associated with GH and preeclampsia. Participants from the Tongji Maternal and Child Health Cohort with information on periconceptional FA supplement use and diagnosis of GH/preeclampsia were included (n=4853). Robust Poisson regression was used to assess the association of FA supplement use and GH and preeclampsia. Among the 4853 participants in this study, 1161 (23.9%) and 161 (3.3%) women were diagnosed with GH and preeclampsia, respectively. The risk ratio of developing GH was higher in women who used ≥800 µg/d FA supplement from prepregnancy through midpregnancy than nonusers (risk ratio, 1.33 [1.08–1.65]). After adjusting for social-demographic, reproductive, lifestyle factors, family history of hypertension, other supplement use, and gestational weight gain, the adverse association remained significant (risk ratio, 1.32 [1.06–1.64]). Restricting the analysis among women with normal weight, without family history of hypertension, and without gestational diabetes mellitus, the positive FA-GH association still existed. We did not find any significant association between FA supplement use and preeclampsia regardless of adjustment. High-dose (≥800 µg/d) FA supplement use from prepregnancy through midpregnancy was associated with increased risk of GH. Attention should be given to avoid the potential risk of GH due to inappropriate FA supplement use in women who are planning or capable of pregnancy. Abstract : Supplemental Digital Content is available in the text.